Cost-utility analysis of vortioxetine versus agomelatine, bupropion SR, sertraline and venlafaxine XR after treatment switch in major depressive disorder in Finland. (4th May 2017) - Soini, Erkki; Hallinen, Taru; Brignone, Mélanie; Campbell, Rosanne; Diamand, Françoise; Cure, Sandrine; Aalto-Setälä, Maria; Danchenko, Natalya; Koponen, Hannu; Kolasa, Katarzyna
ABSTRACT: Background: To assess the cost-utility of vortioxetine versus relevant comparators (agomelatine, bupropion SR, sertraline, and venlafaxine XR) in the finnish setting in major depressive disorder (MDD) patients with inadequate response to selective serotonin- /serotonin–norepinephrine reuptake inhibitors. Methods: A one-year analysis was conducted using a decision tree with a Markov state transition component. The health states were remission, relapse and recovery. A Finnish healthcare payer perspective was adopted. Results: Vortioxetine was less costly and more effective versus all comparators in both direct and societal perspectives. Vortioxetine reduced the average annual direct costs by 4% versus venlafaxine XR and 8% versus sertraline. The greater efficacy associated with vortioxetine was translated into a higher percentage of patients in remission and recovery. The model was most sensitive to changes in remission rates at 8 weeks. Conclusion: This cost-utility analysis showed vortioxetine to be a good alternative for MDD patients switching therapy in Finland.